Management of Denture Infection with Phytomedicine - Anitha, Kuttae Viswanathan; Rajkumar, Krishnan (Infectious disorders drug targets, 2023)
Natural teeth are an integral part of the masticatory system. Absence of dentition subjects the individual to compromised oral function, facial appearance and phonetics. Rehabilitation with dental prosthesis is imperative to restore form and masticatory activity. Currently, fabrication of removable and fixed prosthesis has become most predictable. Nonetheless, there is an increased prevalence of oral stomatitis observed over the years in edentulous individuals wearing removable dentures. Amongst the many pathogens that cause denture infections, Candida albicans is assumed to be the most virulent opportunistic agent. Different methods, such as mechanical, chemical, chemicmechanical, and pharmacological are tried to fight such infections. Regardless of various management strategies developed to treat denture stomatitis, the research continues to evolve the most optimal one. Improper oral and or denture hygiene maintenance, surface irregularities on denture, persistence of xerostomia and associated systemic illness pose risk for exaggeration of the disease. In extreme conditions, the development of aspiration pneumonia in geriatric patients is considered a threat to both dental and medical specialists. Therapeutic administration of synthetic anti-microbial drugs, along with meticulous oral hygiene maintenance are recommended protocols till date. However, limitations such as antibiotic resistance, side effects, counter drug reactions, cost of the medicaments predispose to origin of natural herbal products to treat denture stomatitis. Vast array of plant products are studied in previous literature, yet no definitive edge of one over the other is proven. This article intends to provide a mini-review on the different organic plant materials, also called as phytomedicines used for the treatment of candida associated denture stomatitis (CADS).